2016
DOI: 10.1111/jbi.12734
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogeography of two codistributed subgenera of cave crickets (Orthoptera: Rhaphidophoridae: Ceuthophilus spp.)

Abstract: Aim We compare the phylogeographical structure among caves for co‐occurring cave dwelling crickets (Ceuthophilus) in two subgenera Ceuthophilus (Ceuthophilus) (hereafter, called Ceuthophilus) and Ceuthophilus (Geotettix) (hereafter, called Geotettix). In our study area (central Texas), cave‐inhabiting members of the subgenus Ceuthophilus are trogloxenes, roosting in the caves but foraging above ground and occasionally moving between caves, whereas members of the subgenus Geotettix are near‐obligate cave dwelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…With cave organisms, the majority of research studies have been limited to single species (e.g., Dörge, Zaenker, Klussmann‐Kolb, & Weigand, ; Faille et al., ) or cryptic species complexes with allopatric distributions (e.g., Gómez et al., ; Rastorgueff, Chevaldonné, Arslan, Verna, & Lejeusne, ). Few studies have incorporated phylogeographic approaches that consider intrinsic differences among codistributed cave‐dwelling species (see Pérez‐Moreno, Balázs, Wilkins, Herczeg, & Bracken‐Grissom, ; Weckstein et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…With cave organisms, the majority of research studies have been limited to single species (e.g., Dörge, Zaenker, Klussmann‐Kolb, & Weigand, ; Faille et al., ) or cryptic species complexes with allopatric distributions (e.g., Gómez et al., ; Rastorgueff, Chevaldonné, Arslan, Verna, & Lejeusne, ). Few studies have incorporated phylogeographic approaches that consider intrinsic differences among codistributed cave‐dwelling species (see Pérez‐Moreno, Balázs, Wilkins, Herczeg, & Bracken‐Grissom, ; Weckstein et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Sampling over broader spatial scales, Weckstein et al (2016) found that populations of Ceuthophilus exhibit considerable divergence. Our results suggest that dispersal among C. secretus populations is at least partially tied to the contiguous cave and shelterbearing karst ridges of the region.…”
Section: Discussionmentioning
confidence: 98%
“…Since most populations of C. secretus on FHMR probably consist of hundreds, if not thousands of individuals, effective population sizes may be large enough, even in the absence of fairly robust levels of gene flow, to require many generations of drift for levels of differentiation to reflect recent isolation events (Whitlock and McCauley 1999). Mitochondrial DNA suggests that effective population sizes of Ceuthophilus might be large (Weckstein et al 2016). The observation that site 5 was more similar to eastern NFHR populations, that are separated by a large inlet of Belton Lake, than to populations co-located on NR, would seem to suggest that Belton Lake is too recent of a landscape feature to have erased pre-existing genetic patterns.…”
Section: Landscape Analysesmentioning
confidence: 98%
See 1 more Smart Citation
“…During the process of adaptation to a subterranean medium, animals have indeed fine-tuned their physiological tolerance to the stable condition of their habitat, which hampers their dispersal ability via non-subterranean habitats. Accordingly, studies conducted so far have uncovered pronounced genetic structuring and low gene flow -if any -between cave populations (Caccone 1985, Bohonak 1999, Dixon and Zigler 2011, Mammola et al 2015, Weckstein et al 2016. For these reasons, a small calibration area can be approximated for most subterranean species.…”
Section: Dispersal Characteristicsmentioning
confidence: 99%